Mechanical, corrosion and biocompatibility behaviour of Mg-3Zn-HA biodegradable composites for orthopaedic fixture accessories. (February 2018) - Jaiswal, Satish; Kumar, R. Manoj; Gupta, Pallavi; Kumaraswamy, Murali; Roy, Partha; Lahiri, Debrupa
Abstract: Development of biodegradable implants has grown into one of the important areas in medical science. Degradability becomes more important for orthopaedic accessories used to support fractured and damaged bones, in order to avoid second surgery for their removal after healing. Clinically available biodegradable orthopaedic materials are mainly made of polymers or ceramics. These orthopaedic accessories have an unsatisfactory mechanical strength, when used in load-bearing parts. Magnesium and its alloys can be suitable candidate for this purpose, due to their outstanding strength to weight ratio, biodegradability, non-toxicity and mechanical properties, similar to natural bone. The major drawback of magnesium is its low corrosion resistance, which also influences its mechanical and physical characteristics in service condition. An effort has been taken in this research to improve the corrosion resistance, bioactivity and mechanical strength of biodegradable magnesium alloys by synthesizing Mg-3 wt% Zn matrix composite, reinforced with thermally treated hydroxyapatite(HA) [Ca10 (PO4 )6 (OH)2 ], a bioactive and osteogenic ceramic. Addition of 5 wt% HA is found effective in reducing the corrosion rate by 42% and improvement in the compressive yield strength of biodegradable magnesium alloy by 23%. In-vitro evaluation, up to 56 days, reveal improved resistance to degradation with HA reinforcement to Mg. Osteoblast cells show better growth and proliferation on HA reinforced surfaces of the composite. Mg-HA composite structure shows impressive potential to be used in orthopaedic fracture fixing accessories. Graphical abstract: